1981
DOI: 10.1037/0278-7393.7.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Input, decision, and response factors in picture–word interference.

Abstract: Two variations of the picture-word analogue of the Stroop task were examined in an effort to gain a better understanding of the processes involved in responding to picture-word stimuli. Four stages in this process were outlined and then evaluated as potential sources of the interference in these types of tasks. In Experiment 1 subjects were required to respond yes or no (vocally or manually) to whether the picture was that of a dog. In Experiment 2 subjects were asked to respond by naming the picture's semanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
3
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 21 publications
8
95
3
1
Order By: Relevance
“…Probably the best known work using this task was by Lupker (1979;Lupker & Katz, 1981. In his 1979 paper, he confirmed Rosinski's (1977) finding that same-category words magnified interference relative to either unrelated words or pronounceable nonwords, which caused equivalent interference.…”
Section: Semantic Variation and The Irrelevant Wordmentioning
confidence: 53%
“…Probably the best known work using this task was by Lupker (1979;Lupker & Katz, 1981. In his 1979 paper, he confirmed Rosinski's (1977) finding that same-category words magnified interference relative to either unrelated words or pronounceable nonwords, which caused equivalent interference.…”
Section: Semantic Variation and The Irrelevant Wordmentioning
confidence: 53%
“…In the unstable context retrieval condition, patients with frontal cortical lesions performed significantly worse than control subjects ( p ¼ 0.03), whereas patients with temporal lesions did not differ from controls ( p ¼ 0. 35).…”
Section: Resultsmentioning
confidence: 99%
“…The rectangular contexts were abstract non-verbal coloured designs created for the purpose of this experiment using Adobe Illustrator and Photoshop. It has been demonstrated that semantic similarity, even between pictures and words [35], exerts an interfering influence on retrieval, as concepts compete with one another [36]. Because we wanted no pre-existing relationships (i.e.…”
Section: (C) Experimental Materialsmentioning
confidence: 99%
“…In this framework, the semantic interference effect arises because unrelated distractors can be excluded from production relatively sooner than distractor words corresponding to semantic category coordinates of the target pictures. For example, when naming a picture of a CAR, the semantically related distractor word truck satisfies the semantic criterion of naming a vehicle, whereas the unrelated distractor word Lupker, 1979;Lupker & Katz, 1981).…”
Section: The Response Exclusion Hypothesismentioning
confidence: 99%
“…In this framework, the semantic interference effect arises because unrelated distractors can be excluded from production relatively sooner than distractor words corresponding to semantic category coordinates of the target pictures. For example, when naming a picture of a CAR, the semantically related distractor word truck satisfies the semantic criterion of naming a vehicle, whereas the unrelated distractor word Lupker, 1979;Lupker & Katz, 1981).The response exclusion hypothesis and the hypothesis of lexical selection by competition make different assumptions regarding the locus of the semantic interference effect. According to the hypothesis of lexical selection by competition, the semantic interference effect arises at the level of lexical selection.…”
mentioning
confidence: 99%